Image-Guided Biopsy for Relapsed Neuroblastoma: Focus on Safety, Adequacy for Genetic Sequencing, and Correlation of Tumor Cell Percent With Quantitative Lesion MIBG Uptake. (28th January 2021) - Samoyedny, Andrew; Srinivasan, Abhay; States, Lisa; Mosse, Yael P.; Alai, Emma; Pawel, Bruce; Pogoriler, Jennifer; Shellikeri, Sphoorti; Vatsky, Seth; Acord, Michael; Escobar, Fernando; Edgar, J. Christopher; et al.
Abstract : PURPOSE: Many novel therapies for relapsed and refractory neuroblastoma require tumor tissue for genomic sequencing. We analyze our experience with image-guided biopsy in these patients, focusing on safety, yield, adequacy for next-generation sequencing (NGS), and correlation of tumor cell percent (TC%) with quantitative uptake on 123 I-meta-iodobenzylguanidine (MIBG) single-photon emission computed tomography with computed tomography (SPECT/CT). MATERIALS AND METHODS: An 11-year retrospective review of image-guided biopsy on 66 patients (30 female), with a median age of 8.7 years (range, 0.9-49 years), who underwent 95 biopsies (55 bone and 40 soft tissue) of relapsed or refractory neuroblastoma lesions was performed. RESULTS: There were seven minor complications (7%) and one major complication (1%). Neuroblastoma was detected in 88% of MIBG- or fluorodeoxyglucose-avid foci. The overall NGS adequacy was 69% (64% in bone and 74% in soft tissue, P = .37). NGS adequacy within neuroblastoma-positive biopsies was 88% (82% bone and 96% soft tissue, P = .11). NGS-adequate biopsies had a greater mean TC% than inadequates (51% v 18%, P = .03). NGS-adequate biopsies had a higher mean number of needle passes (7.5 v 3.4, P = .0002). The mean tissue volume from NGS-adequate soft-tissue lesions was 0.16 cm 3 ± 0.12. Lesion:liver and lesion:psoas MIBG uptake ratios correlated with TC% (r = 0.74, r = 0.72, and n = 14). Mean TC% in NGS-adequate samples was 51%, corresponding to a lesion:liver ratio of 2.9 and a lesion:psoas ratio of 9.0. Thirty percent of biopsies showed an actionable ALK mutation or other therapeutically relevant variant. CONCLUSION: Image-guided biopsy for relapsed or refractory neuroblastoma was safe and likely to provide NGS data to guide therapy decisions. A lesion:liver MIBG uptake ratio of ≥ 3 or a lesion:psoas ratio of > 9 was associated with a TC% sufficient to deliver NGS results.